2006
DOI: 10.1007/s10038-006-0380-y
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of five G6PD variants indicates ethnic complexity of Phuket islanders, Southern Thailand

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzymopathy in humans. The prevalence of G6PD deficiency and its molecular basis were studied in Phuket islanders, Southern Thailand. A total of 345 volunteers (123 males and 222 females) were recruited in this study. Infection with Plasmodium falciparum or Plasmodium vivax was not detected in any of these subjects by polymerase chain reaction (PCR)-based diagnosis. G6PD-deficient individuals were identified with the WST-8/1-methoxy PMS met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
2
16
1
Order By: Relevance
“…This mutation is also the second most common mutation in southern Thailand (Laosombat et al 2005). It is found in a few cases of Phuket Islanders in southern Thailand (Ninokata et al 2006) and a few cases of Malaysian Malay (Ainoon et al 2002). The haplotype of Chinese with G6PD Kaiping is also uniformly 1311C and 93T (Yan et al 2006), similar to our Mon case in this study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This mutation is also the second most common mutation in southern Thailand (Laosombat et al 2005). It is found in a few cases of Phuket Islanders in southern Thailand (Ninokata et al 2006) and a few cases of Malaysian Malay (Ainoon et al 2002). The haplotype of Chinese with G6PD Kaiping is also uniformly 1311C and 93T (Yan et al 2006), similar to our Mon case in this study.…”
Section: Discussionsupporting
confidence: 87%
“…G6PD Kerala-Kalyan (949G [ A) was reported to be prevalent (24.9%) in India (Sukumar et al 2004). None of these mutations were found in Thai, Laotians, or Cambodians, whereas G6PD Mediterranean was found in approximately 30% of G6PD-deficient Indonesians from central Java (Soemantri et al 1995), 27% of G6PD-deficient Malaysian Malays (Ainoon et al 2002), occasionally in Thais of the southern province of Thailand (Laosombat et al 2005), and G6PD KeralaKalyan was also identified in Urak-Lawoi, a sea Gypsy population of the Andaman Sea who inhabited Phuket Island in southern Thailand (Ninokata et al 2006). Both polymorphisms C and T are present at nt 1311 in Indians Numbers represent number of G6PD mutations identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it was suggested that the selective advantage of resistance to malaria was counterbalanced with selective disadvantageous results of G6PD deficiency, and this stopped the rise of malaria frequencies in endemic regions (Ruwende, et al, 1995). In another study, Ninokata et al (2006) investigated 345 healthy adults for G6PD deficiency on Phuket Island, which had been determined to be a malaria-endemic region and found out that 10% of these individuals had G6PD deficiency. Interestingly, it was observed that none of the individuals had molecular evidence of malaria infection.…”
Section: Malaria and Glucose-6 Phosphate Dehydrogenase Deficiencymentioning
confidence: 97%
“…Interestingly, it was observed that none of the individuals had molecular evidence of malaria infection. According to this study, researchers postulated that G6PD deficiency provided an advantageous genetic trait against malaria (Ninokata, et al, 2006).…”
Section: Malaria and Glucose-6 Phosphate Dehydrogenase Deficiencymentioning
confidence: 99%